Pengolahan Hasil Asesmen dan Penyusunan Rapor untuk Sekolah Penggerak - Isnawan, Muhamad Galang; Samsuriadi, Samsuriadi; Bahri, Samsul; Shantika, Evana Gina; Indrawati, Indrawati; Lume, Lume; Burhanudin, Burhanudin (Universitas Nusantara PGRI Kediri, 2023)
Sekolah Penggerak are schools that are required to implement the Kurikulum Merdeka. One obstacle that Sekolah Penggerak experienced in implementing the Kurikulum Merdeka is the low competence of school principals and teachers in compiling and processing assessment results and report cards. Workshops are a relatively effective way of developing the competence of school principals and teachers. Therefore, this service aims to strengthen the competence of school principals and teachers regarding assessments and report cards through workshop activities. The workshop was also chosen because it involves direct interaction with participants through relevant worksheets. The participants of the workshop were eighteen people consisting of three junior high school principals, three high school principals, six teachers of the junior high school, and six teachers of the high school who were members learning committee. Workshop activities are carried out for eight lesson hours using worksheets from the government. Data were analyzed using qualitative data analysis. The dedication results show that the workshop activities are going well, especially the discussion activities. Although, the time allocation for activities tends to be more. In general, each school has been able to prepare assessments well, although it is still constrained in making criteria for achieving learning objectives. In addition, the assessment editor designed by the school still needs to be more optimal because there are still schools that compile an assessment rubric for that section. Likewise, when processing the assessment results, it was found that schools needed to be able to formulate a formula to determine student scores. In contrast to the previous results, when participants compiled report cards, information was obtained that all schools could prepare report cards properly, including in compiling descriptions related to student competency achievements.